DOI: 10.3384/diss.diva-138657
|View full text |Cite
|
Sign up to set email alerts
|

Evolving germs – Antibiotic resistance and natural selection in education and public communication

Abstract: Bacterial resistance to antibiotics threatens modern healthcare on a global scale. Several actors in society, including the general public, must become more involved if this development is to be countered. The conveyance of relevant information provided through education and media reports is therefore of high concern. Antibiotic resistance evolves through the mechanisms of natural selection; in this way, a sound understanding of these mechanisms underlies explanations of causes and the development of effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 148 publications
(306 reference statements)
0
6
0
Order By: Relevance
“…The K 648 central star was also observed with the HST's Faint Object Spectrograph (FOS). The unpublished HST/FOS spectrum was kindly provided in electronic form by R. Bohlin (2000), calibrated on the white dwarf scale according to Bohlin (1996) and Bohlin, Lindler, & Keyes (1995). The uncertainty in FOS absolute fluxes are estimated to be ∼5% for this spectrum.…”
Section: Central Star Photometrymentioning
confidence: 99%
“…The K 648 central star was also observed with the HST's Faint Object Spectrograph (FOS). The unpublished HST/FOS spectrum was kindly provided in electronic form by R. Bohlin (2000), calibrated on the white dwarf scale according to Bohlin (1996) and Bohlin, Lindler, & Keyes (1995). The uncertainty in FOS absolute fluxes are estimated to be ∼5% for this spectrum.…”
Section: Central Star Photometrymentioning
confidence: 99%
“…These X-ray arches are closely related to coronal arches observed in visible light above the cavity (Balanovsky and Perepelkin, 1928;Wallenquist, 1957;Leroy and Servajen, 1966;Kawaguchi, 1967;Saito and Hyder, 1968;Fort and Martres, 1974). Furthermore, EUV observations have shown that cavities are evident also in EUV lines formed at coronal temperatures (such as Ne vii and Mg x), while lines typical of the transition region are present at the wominence-corona interface (Noyes et al, 1972;Schmahl et al, 1974;Orrall and Schmahl, 1976;Bohlin, 1976). The presence of these coronal cavities seems to suggest that the prominence material is condensed from the corona.…”
Section: Introductionmentioning
confidence: 99%
“…The limited duration of the learning session (the intervention time was roughly 45 min) may have affected several of the performance results, particularly CINS scores. There are a few studies indicating that learning evolutionary concepts in very short time (i.e., one or two lessons or hours) can result in higher knowledge (e.g., Beardsley et al 2012;Bohlin 2017;Lee et al 2017;Yamanoi and Iwasaki 2015). However, evolution education research also shows that the theory of evolution presents severe problems to learners, which have not been effectively solved by teaching strategies applied to date (e.g., Kampourakis and Zogza 2008;Rosengren et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Concerning this, the timeframe for the intervention was highly restricted. Nevertheless, studies indicated that even short learning periods could improve student's knowledge acquisition (e.g., Bohlin 2017;Eckhardt et al 2013;Yamanoi and Iwasaki 2015). The timeframe should have been fine for investigating the effectiveness of EvoSketch simulations and the respective self-directed instructional support.…”
Section: Limitationsmentioning
confidence: 99%